Are small family firms financially sophisticated? - Di Giuli, Alberta; Caselli, Stefano; Gatti, Stefano (Journal of Banking & Finance, 2011)
We study the drivers of financial sophistication in small family firms. Sophistication is defined as the use of non-basic financial products such as options, swaps, debt restructuring, and mergers and acquisitions (M&A) advisory services. Our analysis is based on a unique dataset with detailed information on 187 Italian family firms. We find that the main drivers of financial sophistication are: (1) the generation that currently owns the firm; (2) the presence of a non-family CFO; and (3) the existence of a non-family shareholder. We analyze the impact of these factors on the following four classes of non-basic financial products: corporate finance, cash management, corporate lending and risk management. Our results can be used to determine the characteristics of financially sophisticated family firms and whether their corporate governance and ownership structure increase the use of non-basic financial products.